Accountability for Reasonableness, for Priority Setting and Resource Allocation: A Case Scenario (Bangladesh Journal of Bioethics, 2015)
The purpose of this paper is to discuss the accountability for reasonableness and its four conditions. This explains the priority setting and resource allocation for scarce resources. In this article it is discussed that how the scarce resources in a developing country like Pakistan be allocated in health care. This is explained with the help of case scenario.